Application of Eigenvector and Eigenvalue for face recognition / Redhayuden Aidil Abdul Razak - Abdul Razak, Redhayuden Aidil (2020)
Face recognition is becoming one of the major aspects in computer vision. Face Recognition have various applications including Security Systems, Augmented reality, Real time identification and many more. Over the past few decades there have been numerous works done in this field and many methods and algorithms have been proposed. Although a revolutionary progress has been made regarding face recognition under usual circumstances and small variations but when it comes to recognizing faces in extreme variations like lighting and facial expressions the accuracy of the systems decreases dramatically. In this research, application of Eigenvector and Eigenvalue will be discussed for face recognition and execute a simple program using MATLAB. Furthermore, the accuracy of Eigenface will be shown and discussed at the end of the chapter.